2002
DOI: 10.1023/a:1021357506703
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In aqueous medium etiolated wheat seedlings release superoxide anion (O2*-). Interaction of a synthetic antioxidant, butylated hydroxytoluene (BHT, ionol), with oxygen in the aqueous medium is accompanied by O2*- formation. This suggests that under certain conditions BHT behaves as a prooxidant. A natural antioxidant, superoxide dismutase (SOD), and also a wound healing preparation, emulsified denatured placenta (EDP), do not exhibit the prooxidant properties. In contrast to BHT, they reduce O2*- production by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In our case, BHT acting as prooxidant interacts with molecular oxygen rather than with O 2 •− radical. This reaction yields phenoxyl radical and superoxide anion [6]. Deeper oxidation of BHT may result in formation of BHT quinone methide and other products of BHT oxidation which can also generate superoxide anion [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, BHT acting as prooxidant interacts with molecular oxygen rather than with O 2 •− radical. This reaction yields phenoxyl radical and superoxide anion [6]. Deeper oxidation of BHT may result in formation of BHT quinone methide and other products of BHT oxidation which can also generate superoxide anion [6].…”
Section: Resultsmentioning
confidence: 99%
“…•− ) can be formed due to direct interaction of BHT with molecular oxygen [6]; as a consequence, a high oxidative stress was caused as indicated by the decrease in the activities of SOD and CAT (Figs. 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the above-mentioned studies suggest a prooxidant activity, there is limited information available concerning the conditions and the mechanisms under which BHT exerts a prooxidant behavior. Some authors have reported that at high aeration rate, BHT can react with molecular oxygen rather than with the reactive oxygen species present, yielding BHT-phenoxyl radical and superoxide anion (Smirnova andothers 2002, Nanou andothers 2010). The reaction pathways proposed for BHT prooxidant activity are summarized in Figure 1.…”
Section: Bht and Its Metabolites As Antioxidants Or Prooxidantsmentioning
confidence: 99%
“…These two variants of the plant immersion into the incubation medium gave qualitatively similar results. According to [7], superox ide dismutase fully converted the generated О 2 into hydrogen peroxide. Incubation was performed in the dark at 26°C for 1 h. Then the seedlings were taken out from the incubation medium, and the quantity of formazan was determined in it (superoxide anion released by the seedling in the aqueous medium reduced NBT to for mazan) at the wavelength of 530 nm.…”
Section: Methodsmentioning
confidence: 99%